Structural Features of the Homeric Hymns - Kardelis, Naglis (Literatūra, 2012)
The author of the article presents a structural analysis of the Homeric Hymns. Drawing on the results of a research based upon a quantitative approach, that is, calculation of various formal textual parameters supplemented by a qualitative interpretation of achieved results, he discusses the structural features of the corpus of the Homeric Hymns as a textual whole, the distribution of the hymns according to the dedications attached to them, i. e. according to their divine or heroic addressee, and the structural framework of the hymns of different length. First of all, in the first chapter of the article, which serves as an introduction to the investigative part of this paper (the presentation of the results of the research proper), the author briefly discusses the historical process of the formation of the Hymns’ corpus and some other textological issues relevant to the ensuing research. After that, in the second chapter of the article, the author focuses on the compositional structure of the whole corpus of the Homeric Hymns, suggesting a hypothetical scheme of dividing the overall narrative sequence of the whole corpus of the Homeric Hymns into eight sequential groups. It is argued that each of these sequential groups has a unity of its own,which might be described in terms of both form and content. Special attention is given to the admirably smooth transition from almost any one sequential group to the next one. In the third chapter, the author discusses the distribution of the Hymns according to their dedication, i. e. according to their divine or heroic addressee. Presenting an interpretation of the quantitative results arrived at in this chapter, the author suggests some possible answers (or, rather, only some clues) as to why some ancient Greek deities are given in the Homeric Hymns much more attention than others (for example, why some especially prominent Greek gods, say, Zeus, Poseidon, or Hades, are made to stand in the shadow of some subordinate or even minor, if not marginal, deities). In the fourth chapter of the article, the author focuses on the structural framework of typical individual hymns of different length. During this stage of the research, the author posits five typical groups of the hymns according to their length and briefly discusses the specific features of the hymns belonging to these five groups in terms of their form, content, and a correlation between their form and content. At the end of the article, the conclusion is made that some kind of a quantitative approach to the Homeric Hymns, for example, such as presented in this paper, if correctly conducted and creatively interpreted, might present us valuable fresh insights into the structural nature of the corpus of the Homeric Hymns as a whole, as well as shed some light on the problems of the structure of individual hymns. As a consequence of these deeper insights, we find ourselves in a situation where we should abandon all talk about the so-called structural chaos of the Homeric Hymns.